Assessment of water quality variation of a monitoring network using exploratory factor analysis and empirical orthogonal function. (August 2017) - Kim, Sung Eun; Seo, Il Won; Choi, Soo Yeon
Abstract: This study suggests a systematic assessment method that jointly uses the exploratory factor analysis (EFA) and empirical orthogonal function (EOF-patterns) of Principal Component Analysis (PCA) to assess the water quality variation of the monitoring network of Nakdong River, Korea, in which 28 stations measuring 15 water quality parameters are located. The EFA results showed the monitoring stations to be distinguished by two main factors. The representative stations of which the variance was almost explained by the specific factor were selected. We applied PCA to the monitoring data of representative stations, and then analyzed the EOF-patterns that indicate the characteristics of water-quality variation for each factor. With the interpretation of main factors and EOF-patterns causing dominant water quality variations, the monitoring network of Nakdong River could be spatially and seasonally evaluated according to the contribution of each factor. Highlights: The water quality variation of a monitoring network was assessed. Exploratory Factor Analysis (EFA) and Empirical Orthogonal Function (EOF) were used. The EFA was applied to distinguish the monitoring stations by main factors. The EOF-patterns showed the water-quality variation characteristics for each main factor. The results agreed well with the reported water-quality characteristics of the river.